1972
DOI: 10.1002/aja.1001340103
|View full text |Cite
|
Sign up to set email alerts
|

Retinal damage after prolonged exposure to visible light. A light and electron microscopic study

Abstract: Albino rats were exposed to fluorescent illumination for four to six months at an intensity which would not cause photocoagulation of the retina. Electron and light microscopic studies indicated that the retinas of these animals were irreversibly damaged and that the degeneration was specifically localized to the photoreceptor cells. Photoreceptors were not found in any of these retinas. Prolonged exposure to low intensity, visible light had no apparent effect on the bipolar neurons and ganglion cells or on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
2

Year Published

1973
1973
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(28 citation statements)
references
References 11 publications
3
22
0
2
Order By: Relevance
“…3D). Our results are thus in agreement with previous studies that showed a significant impairment in retinal structure [5,7] and function [33][34][35] following chronic light exposure. Persistence of a residual photopic b-wave (in responses evoked to the brightest stimuli; Table 1) indicates that cones were more resistant than rods, a claim also previously advanced by others [36][37][38].…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…3D). Our results are thus in agreement with previous studies that showed a significant impairment in retinal structure [5,7] and function [33][34][35] following chronic light exposure. Persistence of a residual photopic b-wave (in responses evoked to the brightest stimuli; Table 1) indicates that cones were more resistant than rods, a claim also previously advanced by others [36][37][38].…”
Section: Discussionsupporting
confidence: 96%
“…For example, as little as one hour of light exposure is sufficient to yield ultrastructural changes at the photoreceptors as documented with electron microscopy [7,8]. Extending the exposure to 24 h will cause severe and irreversible functional and structural (histological) damages to the retina of adult rats such as a complete extinction of the ERG as well as a concomitant marked reduction in the thickness of the ONL [9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Our data are in agreement with those reported by Noell et al (1966), O'Steen (1970), O'Steen et al (1972), and Rapp and Williams (1980). Since the Brown Norway rats received the same light treatment and were exposed to the same ambient temperature as the Sprague-Dawley rats, we suggest that all changes in tissue levels observed in Sprague-Dawley rats are most likely due to the damaged retina in the albino rats.…”
supporting
confidence: 95%
“…The 24:0 light cycle was attained by keeping the animals in ventilated cabinets with overhead cool white fluorescent light sources producing an irradiance of 750 ± 150 gW/cm2; this irradiance of constant light has been shown to induce photorecep tor atrophy [3,7,8,13]. On the night of the experiment, groups of 6 or 7 rats each, weighing approximately 250 g, from both the 14:10 and the 24:0 cycles, were killed in the dark, or after exposure to cool white fluorescent light irradiances of 0.0005,0.175 or 3.33 gW/ cm2 for 15 or 30 min.…”
Section: Experiments Imentioning
confidence: 99%
“…Light influences the gland by means of a multisynaptic neural pathway which connects the retinas to the pineal [12], Previous studies indicate that the sensitivity of the pineal to light may vary according to the animals' previ ous lighting history [14]. In comparative studies, pineal serotonin N-acetyltransferase (NAT) activity and melat onin levels in diurnally active animals, such as the Richard son's ground squirrel [18] and the Eastern chipmunk [16], are much less sensitive to light inhibition than are those of nocturnally active rodents such as the Syrian hamster [4] and the cotton rat [22], Long-term light exposure causes severe photoreceptor damage and degeneration in the retinas of albino rats [7,8,13]. These animals still, however, are sensitive to light-in duced pineal inhibition when exposed to alternating light…”
mentioning
confidence: 99%